Returns and Volatility of Low-Grade Bonds: 1977-1989. - Blume, Marshall E; Keim, Donald B; Patel, Sandeep A (Journal of Finance, 1991)
This paper examines the risks and returns of long-term low-grade bonds for the period 1977-89. The authors find (1) low-grade bonds realized higher returns than higher-grade bonds and lower returns than common stocks, and low-grade bonds exhibited less volatility than higher-grade bonds due to their call features and high coupons; (2) there is no relation between the age of low-grade bonds and their relaxed returns; cyclical factors explain much of the observed reaction between default rates and bond age; and (3) low-grade bonds behave like both bonds and stocks. Despite this complexity there is no evidence that low-grade bonds are systematically over- or under-priced.